2000
DOI: 10.1029/1999gb900101
|View full text |Cite
|
Sign up to set email alerts
|

Winter fluxes of greenhouse gases from snow‐covered agricultural soil:intra‐annual and interannual variations

Abstract: Abstract. Despite the length of winter in cold temperate climates, few studies refer to greenhouse gas emissions from soils during the nongrowing season. In this study, N20 and CO2 fluxes from agricultural and forest soils in southeastern Quebec (Canada) were measured during winter and spring from 1994 to 1997, and the influences of climate, soil, and snow properties on the gaseous emissions were examined. N20 fluxes were far greater from the agricultural soil (2-187 ng N20 m -2 s 'l) than from the forest soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 28 publications
3
38
1
Order By: Relevance
“…Therefore, the CO 2 flux was equally dependent on surface conditions as subsurface conditions. The CO 2 is likely produced throughout the soil profile when there is sufficient available substrate but unlike N 2 O, the CO 2 does not become consumed or altered as it travels to the surface (Van Bochove et al, 2000). This also supports the suggestion of surface N 2 O production, since if N 2 O was trapped and released upon thaw, CO 2 would be undergoing the same process.…”
Section: N 2 O and Co 2 Flux Comparisonssupporting
confidence: 65%
See 3 more Smart Citations
“…Therefore, the CO 2 flux was equally dependent on surface conditions as subsurface conditions. The CO 2 is likely produced throughout the soil profile when there is sufficient available substrate but unlike N 2 O, the CO 2 does not become consumed or altered as it travels to the surface (Van Bochove et al, 2000). This also supports the suggestion of surface N 2 O production, since if N 2 O was trapped and released upon thaw, CO 2 would be undergoing the same process.…”
Section: N 2 O and Co 2 Flux Comparisonssupporting
confidence: 65%
“…Conditions at depth in the soil profile (!20 cm) are also conducive to denitrification and N 2 O production, as evidenced by high concentrations measured during winter (Burton and Beauchamp, 1994;Van Bochove et al, 2000). Such high N 2 O concentrations were also observed at our site during January to March 2003(Hu, 2006.…”
Section: N 2 O and Co 2 Flux Comparisonsmentioning
confidence: 57%
See 2 more Smart Citations
“…These emissions can be a major component of annual N 2 O emissions but the magnitude of emissions can differ greatly between years at a given site. For example, Van Bochove et al (2000) found that measured fluxes ranged from 0.4 kg N 2 O-N ha -1 in 1995-1996 to 10 kg N 2 O-N ha -1 in 1996-1997 for their study on winter fluxes from snow-covered agricultural fields in Quebec. Differences in snowmelt emissions among land uses and topographical positions have also been documented.…”
mentioning
confidence: 99%